Transmission network expansion planning considering HVAC/HVDC lines and technical losses - Dominguez, Andres H. (2017)
This paper presents a mixed-integer linear programming (MILP) model to solve the transmission network expansion planning problem considering HVAC/HVDC links and power system losses. use of an MILP model guarantees convergence to optimality by using existing classical optimization methods. model was implemented using the modeling language AMPL and solved using the solver CPLEX. proposal was tested with the southern Brazilian electrical system of 46 buses and 79 candidate lines. losses of both AC and DC lines are modeled as piecewise linear functions of the line flows. DC transmission system may use either current source converters or voltage source converters. Sensitivity analysis for the cost of energy and planning horizon time were performed. results show that DC links have the potential to be included in power system planning problems.